2015
DOI: 10.1002/sia.5784
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial reactions of a MAX phase/superalloy hybrid

Abstract: Oxidation resistant, strain tolerant MAX phase coatings are of general interest for high temperature applications. Accordingly, Cr 2 AlC MAX phase coupons were vacuum diffusion bonded to an advanced turbine disk alloy at 1100°C for compatibility studies. The interface revealed an inner diffusion zone consisting of~10 μm of β-Ni(Co)Al, decorated with various γ′ (Ni,Co) 3 Al, Ta(Ti,Nb)C, and W(Cr,Mo) 3 B 2 precipitates. On the Cr 2 AlC side, an additional~40-μm Al-depletion zone of Cr 7 C 3 formed an interconnec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…However, diffusion of elements such as Co, Ti, and Mo from the substrate are detected in the carbide and Cr 2 AlC phases. Diffusion of metallic elements from the substrate has been already reported by Smialek's and Barsoum's groups under other thermal conditions and using other superalloys . Among the different tested MAX phases, Cr 2 AlC shows the lowest diffusion rate, but it is still the main problem to use these compounds in real applications at high temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, diffusion of elements such as Co, Ti, and Mo from the substrate are detected in the carbide and Cr 2 AlC phases. Diffusion of metallic elements from the substrate has been already reported by Smialek's and Barsoum's groups under other thermal conditions and using other superalloys . Among the different tested MAX phases, Cr 2 AlC shows the lowest diffusion rate, but it is still the main problem to use these compounds in real applications at high temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the self‐healing capability at high temperature of Al‐based MAX phases may play an important role in case of a crack penetrating into the bond coat layer . Nevertheless, one of the potential drawbacks for using MAX phases as bond coat is the inner diffusion of metallic elements from the superalloy substrate . In that case, Cr 2 AlC is the most promising composition since it exhibits lower diffusion rates and better compatibility with superalloys than Ti 2 AlC …”
Section: Introductionmentioning
confidence: 99%
“…According to the prior analysis, this will be sufficient to skew oxidation behaviour significantly towards non-protective Ti, Cr-rich rather than protective Al-rich external scales expected for single crystals. 20,21 For example, Equation 6 predicts a weight loss of ~270 mg/cm 2 for LSHR compositions and implies much more severe oxidation than ~1 mg/cm 2 projected for single crystals. This provides another incentive for a hybrid disk concept proposing a bonded outer rim of single crystal elements.…”
Section: Multi-element Variations; Response Surfaces On 3-d Plotsmentioning
confidence: 99%
“…The MoAlB single crystals were shown to have a relatively low hardness (10-13 GPa) compared to most TMBs [19,20] and high room-temperature electrical conductivity [16,19]. In addition to its excellent oxidation resistance, our recent work on bulk MoAlB has shown that it has high electrical and thermal conductivities, room-temperature compressive strengths that are close to 2 GPa, and a thermal expansion coefficient of −9.6 × 10 −6 K −1 -that is comparable to many other engineering materials (e.g., alumina, yttria-stabilized zirconia, and Ni superalloys) [13,21]. In combination, these properties bode well for the use of MoAlB in HT applications.…”
Section: Introductionmentioning
confidence: 99%